2017
DOI: 10.6018/300561
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de dos formatos instructivos, Educación Deportiva e Instrucción Directa, en la respuesta psicológica de estudiantes de secundaria

Abstract: Resumen: El objetivo de este estudio fue examinar los efectos de dos formatos instructivos, Educación Deportiva e Instrucción Directa, en la respuesta psicológica de un grupo de estudiantes de secundaria. 217 (113 varones, 104 mujeres) estudiantes (12-17 años) de un colegio urbano (de 1º a 4º ESO) accedieron a participar. En cada nivel, todos los sujetos fueron distribuidos aleatoriamente en dos grupos de estudio: el grupo experimental experimentó Educación Deportiva y el grupo comparativo experimentó Instrucc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
3
0
3
Order By: Relevance
“…For this reason, the IM values in the quantitative analysis cannot be attributable to the intervention. Other studies have shown an improvement in IM after the application of the SEM, both in secondary students [19,36] and in Baccalaureate students [37].…”
Section: Discussionmentioning
confidence: 85%
“…For this reason, the IM values in the quantitative analysis cannot be attributable to the intervention. Other studies have shown an improvement in IM after the application of the SEM, both in secondary students [19,36] and in Baccalaureate students [37].…”
Section: Discussionmentioning
confidence: 85%
“…La hipótesis planteada sobre las necesidades psicológicas básicas queda confirmada de forma parcial mediante la mejora significativa de la satisfacción de competencia y relación con los demás. Estos hallazgos se encuentran en línea con los de otros trabajos que también encontraron un aumento significativo en la percepción de competencia (Cuevas et al, 2015;Fernández-Río, Méndez-Giménez, & Méndez-Alonso, 2017;Spittle & Byrne, 2009) o sobre la necesidad de relación (Méndez-Giménez et al, 2015;Méndez-Giménez, Martínez de Ojeda, & Valverde-Pérez, 2017;Perlman, 2010;. Salvo el trabajo de Perlman (2011), estos estudios compararon las repercusiones del MED frente a las de la enseñanza tradicional, constatando mejores efectos en el alumnado que había experimentado el MED.…”
Section: Discussionunclassified
“…2022) can be highlighted. In these studies, school interventions had significant improvements in variables such as intrinsic motivation, autonomy, competence, social relationships, novelty satisfaction, interest, boredom, social responsibility, behavioral and emotional involvement, teamwork, and perceived gender differences and inequalities in PE (for more information see Fernández-Río et al, 2017;Gil-Arias et al, 2017;Gil-Arias et al, 2020;Llanos-Muñoz et al, 2022).…”
Section: Ultimate Frisbee Through Sport Education Modelmentioning
confidence: 99%